A Tentorial Venous Hemangioma Presenting As an Extra-Axial Mass in the Ambient Cistern: A Case Report - Oya, Soichi; Prayson, Richard A.; Lee, Joung H. (Journal of Neurological Surgery Reports, 2012)
Although venous hemangiomas are one of the most common soft-tissue tumors, venous hemangiomas in the central nervous system are extremely rare. We present an unusual case of venous hemangioma originating from the interdural space of the tentorium. A 32-year-old woman was incidentally found to have extra-axial mass occupying the left ambient cistern. This tumor was observed for the first 4 years as it was completely asymptomatic. Surgical resection was later recommended when the tumor grew. The mass originated from between the two layers of the anteromedial tentorial incisura. There were no findings indicative of previous hemorrhage inside the mass. The matrix of the mass was firm and vascular, resembling a fibrous meningioma. Gross total resection was achieved without any neurological deficit. Pathological examination revealed a dense fibrous connective tissue with a proliferation of vessels marked by thickened walls. A spindle cell proliferation in the vessel walls did not stain with the antibody to S-100 protein. Movat stain demonstrated the venous character of the vessels. These results were histologically compatible with a venous hemangioma. Albeit extremely rare, a venous hemangioma, a distinct clinical and pathological entity from a venous angioma, can present an intracranial mass lesion.
Keywords: ambient cistern; extra-axial; tentorium; vascular tumor; venous hemangioma